Assessment and management of impacted teeth in adolescent patients (Research, Society and Development, 2023)
An impacted tooth is completely or partially covered by mucosa and bone for more than 2 years after the physiological eruption time. Impacted teeth are a common dental abnormality seen clinically, although the prevalence varies from location to location and from tooth to tooth. Third molars are the most prevalent impacted teeth, followed by upper canine teeth. In this context, this article aimed to review the literature on the evaluation and management of included elements in adolescent patients. For the construction of this article, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. The articles were contemplated between the years 2000 to 2022. Proper management of impacted teeth is a useful tool for the dentist. Proper classification and terminology can aid communication and allow the practitioner to anticipate more difficult cases. The indications and benefits of extracting impacted teeth prophylactically outweigh the potential complications. The arsenal of instruments and the appropriate surgical technique guarantee the success of the professional and help to improve the patient's results.